Inter-Individual Variability in The Joint Negative Work During Running - Hashizume, Satoru; Hobara, Hiroaki; Kobayashi, Yoshiyuki; Tada, Mitsunori; Mochimaru, Masaaki (Sports Medicine International Open, 2018)
The inter-individual variability of running technique is an important factor affecting the negative work of lower extremity joints that leads to muscle damage. Our study examines the relationships between the negative work of the lower extremity joints and the associated mechanical parameters that account for inter-individual variability in the negative work. Twenty-four young male adults were asked to run on a runway at a speed of 3.0 m·s−1. Multiple linear regression analysis was conducted to examine the relationships between the negative work and the associated mechanical parameters for each lower extremity joint. With regards to the results, 76.3% of inter-individual variability in the negative work of the hip joint was accounted for by inter-individual variabilities in the corresponding moment (25.4%) and duration (50.9%). For the knee joint, the inter-individual variabilities in the moment (40.6%), angular velocity (24.5%), and duration (23.8%) accounted for 88.9% of inter-individual variability in the negative work. The inter-individual variability in the moment of the ankle joint alone accounted for 89.3% of the inter-individual variability in the corresponding negative work. These results suggest that runners can change the negative work by adapting their running techniques to influence the relevant mechanical parameter values; however, major parameters corresponding to the change in the negative work are not the same among the lower extremity joints.
Keywords: running-related injury; lower extremity joint; inverse dynamics; multiple linear regression analysis